MONITORING OF VERTICAL GROUND SURFACE MOVEMENT IN THE COASTAL AREA OF CILACAP REGENCY USING THE SMALL BASELINE SUBSET INTERFEROMETRY SAR (SBAS INSAR) METHOD - Luluk Sabdu Busoroh; Hidayat Panuntun (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2025)
Cilacap Regency on the south coast of Java Island is prone to land movement due to its risky rock formation structure. Previous research found land subsidence in the coastal area of Cilacap District at -70 mm/year in the satellite view direction. The movement in the satellite view direction is not representative enough to show vertical movement directly. Thus, vertical movement in the coastal area of Cilacap Regency was calculated using the InSAR method. The data used is an unwrapped interferogram image of Sentinel-1 ascending and descending orbit from 2014 to 2024. Noise correction due to tropospheric delay is done with GACOS data. The data was processed using the Small Baseline Subset Interferometry SAR method with LiCSBAS software. Vertical movement was obtained via 2.5-D extraction from ascending and descending Line of Sight (LOS) displacement results and validated with GNSS CORS data of the CCLP station. The results show uplift on the south coast and subsidence in the northern part of Cilacap, with cumulative vertical displacement between -42.823 mm and 50.968 mm and velocities between -4.070 mm/year and 6.349 mm/year. Validation shows 2.5-D InSAR estimates are consistent with GNSS data.Keywords : Vertical Displacement, InSAR, LiCSBAS, Time Series, Cilacap